Discovering millions of plankton genomic markers from the Atlantic Ocean and the Mediterranean Sea. (27th February 2019) - Arif, Majda; Gauthier, Jérémy; Sugier, Kevin; Iudicone, Daniele; Jaillon, Olivier; Wincker, Patrick; Peterlongo, Pierre; Madoui, Mohammed‐Amin
Abstract: Comparison of the molecular diversity in all plankton populations present in geographically distant water columns may allow for a holistic view of the connectivity, isolation and adaptation of organisms in the marine environment. In this context, a large‐scale detection and analysis of genomic variants directly in metagenomic data appeared as a powerful strategy for the identification of genetic structures and genes under natural selection in plankton. Here, we used discosnp ++, a reference‐free variant caller, to produce genetic variants from large‐scale metagenomic data and assessed its accuracy on the copepod Oithona nana in terms of variant calling, allele frequency estimation and population genomic statistics by comparing it to the state‐of‐the‐art method. discosnp ++ produces variants leading to similar conclusions regarding the genetic structure and identification of loci under natural selection. discosnp ++ was then applied to 120 metagenomic samples from four size fractions, including prokaryotes, protists and zooplankton sampled from 39 tara Oceans sampling stations located in the Atlantic Ocean and the Mediterranean Sea to produce a new set of marine genomic markers containing more than 19 million of variants. This new genomic resource can be used by the community to relocate these markers on their plankton genomes or transcriptomes of interest. This resource will be updated with new marine expeditions and the increase of metagenomic data (availability: http://bioinformatique.rennes.inria.fr/taravariants/ ).